Agricultural landscape management strategies in watersheds towards resilient agroecosystems - Tigin Dariati; Kahar Mustari; Muchtar Salam Solle; Fachirah Ulfa; Hari Iswoyo (Future Science, 2021)
A resilient and sustainable agriculture must be able to meet the needs of food for people while taking into account the state of the ecosystem. Aims of this study is to develop a suitable management strategy to be applied to the agricultural landscape in the upstream of Jeneberang watershed in order to form a resilient agroecosystem. This research is a descriptive-analysis research. In this study, information was collected regarding the development of agricultural and agroecosystem activities in the upstream of the Jeneberang watershed. The data used were derived from primary data and secondary data. Primary data obtained from interviews and distributing questionnaires to respondent farmers, as well as field surveys. Meanwhile, secondary data retrieved from literature studies and data from various related agencies. Several strategies for managing agricultural landscapes towards resilient agroecosystems in the upstream Jeneberang watershed are as follows: diversify agricultural crops and agricultural activities in the upstream Jeneberang watershed; combine the use of environmentally friendly technology to make it suitable for the land; build good communication among the community; and develops agrotourism or ecotourism activities.